3D printing with light - Xiao, P.; Xiao, Pu; Xiao, Pu; Zhang, Jing; Zhang, Jing (De Gruyter, 2021)
The book introduces fundamentals of 3D printing with light, photoinitiating system for 3D printing as well as resins. Plenty of applications, trends and prospects are also discussed, which make the book an essential reference for both scientists and industrial engineers in the research fields of photochemistry, polymer chemistry, rapid prototyping and photopolymerization.